Monday

January 23, 2017
Posted by **Angela** on Wednesday, May 16, 2012 at 1:04am.

-4(t+7)-(t+6)=10

the solution t is:

- Algebra -
**Bosnian**, Wednesday, May 16, 2012 at 1:50am- 4 ( t + 7 ) - ( t + 6 ) = 10

- 4 * t - 4 * 7 - t -+ 6 = 10

- 4 t - 28 - t - 6 = 10

- 5 t - 34 = 10 Add 34 to both sides

- 5 t - 34 + 34 = 10 + 34

- 5 t = 44 divide both sides by - 5

t = - 44 / 5 = - 8.8

- 4 ( t + 7 ) - ( t + 6 ) = 10

- 4 ( - 8.8 + 7 ) - ( - 8.8 + 6 ) = 10

- 4 * ( - 1.8 ) - ( - 2.8 ) = 10

7.2 + 2.8 = 10

10 = 10